Exercise algebra.manipulation.exponential.equation

Description
solve exponential equation algebraically

Derivation

2*sqrt 2 == 4^(2*x-3)
algebra.manipulation.exponents.factor-as-power
2*sqrt 2 == (2^2)^(2*x-3)
algebra.manipulation.exponents.write-as-power
2*2^(1/2) == (2^2)^(2*x-3)
algebra.manipulation.exponents.mul-exponents
2*2^(1/2) == 2^(2*(2*x-3))
algebra.manipulation.exponents.simple-add-exponents
2^(3/2) == 2^(2*(2*x-3))
algebra.manipulation.exponents.equation.same-base
3/2 == 2*(2*x-3)
algebra.equations.linear.distr-times
3/2 == 4*x-6
algebra.equations.coverup.onevar.minus-left
15/2 == 4*x
algebra.equations.coverup.times
15/8 == x
algebra.equations.linear.flip
x == 15/8